Axenic culture of Trypanosoma cruzi amastigotes as a model for differential metabolic characteristics in the intracellular parasite form - Prego, Alejo Facundo (2023)
Trypanosoma cruzi has a complex life cycle, alternating between an insect vector and the human host, with three well-defined stages: epimastigotes, trypomastigotes, and amastigotes. The stages present in humans are bloodstream trypomastigotes, which is the infective but non-replicative form, and amastigotes, the intracellular replicative form, which are the focus of clinical treatments. Currently, there are two drugs used for treatment: benznidazole (Bz) and nifurtimox. These drugs must be metabolized by the parasite, so they can have an effect, and have a high degree of toxicity to the patient, often leading to treatment abandonment. Recently, the presence of dormant amastigotes within infected cells was described, and they are considered one of the possible causes of therapeutic failure due to their low or null metabolic activity, being able to resist Bz treatment, redifferentiate into trypomastigotes, and reinfect, causing disease relapse. Previous studies described a strategy to differentiate trypomastigotes into amastigotes axenically, using an acidic medium, and maintaining them in this state for a short period (10 days). In this study, we describe a new formulation that allows doubling the cultivation time of axenic amastigotes while preserving their ability to differentiate into trypomastigotes and maintaining their infective potential, similar behavior as dormants. Additionally, we observed signs of a more active metabolism in amastigotes obtained from infected Vero cell cultures, as opposed to those obtained through in vitro differentiation. Therefore, it is necessary to expand studies to determine whether using axenic amastigotes as a model for cultured amastigotes is equivalent or if they would exhibit reduced metabolic activity, making them more similar to dormants.